NEW BATCH OF 2016/2017 USM MEDICAL DOCTORS TO REGISTER IN BELGAUM, INDIA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, 3 September 2016 – The first group of 25 USMKLE students to undergo their undergraduate studies in Medicine has safely arrived in Belgaum on 2 September at 11.45 pm.